PENGARUH STRES KERJA TERHADAP KOMITMEN ORGANISASI MELALUI PERAN PERSEPSI DUKUNGAN ORGANISASI PADA PEGAWAI DALAM KONDISI PANDEMI (Studi Pada Puskesmas Se-Kabupaten Tegal) - Nursyah, Ridwan; Lukiastuti, Fitri (ANALISIS, 2022)
The purpose of this study were to analyze influence of job stress on organizational commitment, to analyze influence of job stress on perceived organizational support, to analyze influence of perceived organizational support on organizational commitment, and to analyze influence of job stress on organizational commitment through perceived organizational support. Population was all Public Health Center employees in Tegal Regency as many as 1,165 employees. Sampling technique used purposive sampling with criteria that employees who are members of the implementing team of task force for the acceleration of handling COVID-19 and vaccination and employees who are willing to fill out this research questionnaire. Rresults show that work stress has no influence on organizational commitment, work stress has a negative and significant influence on perceptions of organizational support, perceptions of organizational support have a positive and significant influence on organizational commitment, work stress has a negative and significant influence on organizational commitment through perceptions of organizational support.